-2(3-4x)-7(x+2)=

Simple and best practice solution for -2(3-4x)-7(x+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(3-4x)-7(x+2)= equation:


Simplifying
-2(3 + -4x) + -7(x + 2) = 0
(3 * -2 + -4x * -2) + -7(x + 2) = 0
(-6 + 8x) + -7(x + 2) = 0

Reorder the terms:
-6 + 8x + -7(2 + x) = 0
-6 + 8x + (2 * -7 + x * -7) = 0
-6 + 8x + (-14 + -7x) = 0

Reorder the terms:
-6 + -14 + 8x + -7x = 0

Combine like terms: -6 + -14 = -20
-20 + 8x + -7x = 0

Combine like terms: 8x + -7x = 1x
-20 + 1x = 0

Solving
-20 + 1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '20' to each side of the equation.
-20 + 20 + 1x = 0 + 20

Combine like terms: -20 + 20 = 0
0 + 1x = 0 + 20
1x = 0 + 20

Combine like terms: 0 + 20 = 20
1x = 20

Divide each side by '1'.
x = 20

Simplifying
x = 20

See similar equations:

| 4y+16=2r | | 16x-10=22 | | 8b-45=-40+7b | | 7(9-7(8-q))-9=9(7(9q-8)+6)-82 | | (5x+3y)(3x+5y)=0 | | 1=3(4k+3)-4k | | 20w-27=-11+19w | | 64.70=4.95+11.95x | | -2y-20=-4-3y | | 6v-2v=24 | | (x+6)(x-6)=28 | | 2v+8-5v=-28 | | 15x-16=33+14x | | 3x=4x+52 | | 16f+23=36+15f | | 5v-15=11+4v | | 2a-5=2a-3 | | 6w-17=27+5w | | 3x+1=5x-12 | | 2.5y+8.4=-20.6 | | 11z-26=-10+10z | | 2(2b-4)-3b=8-4(2-5b) | | 3x+8(2x-6)=2+14 | | A*9fora=2 | | 0.75*5x-x=8.25 | | 10a-9=43+9a | | -7(a-6)=7(a-4) | | -2z+13=45-3z | | -(4b-2)=18-2b | | 10(-5+x)-3=17 | | 3x+5x=30+6 | | -5x+14x=48+24 |

Equations solver categories